Giving condoms to school children: educators' views on making condoms available in South African schools. Issue 1 (2nd January 2022) - Junck, Leah D; George, Gavin
Abstract : One of the policy goals of the South African Department of Basic Education's National Policy on HIV, STIs and TB of 2017 is to reduce the incidence of HIV and pregnancy among learners. This is expected to be achieved by improving access to prevention services, including the provision of condoms in schools. This study uses street- level bureaucracy theory to explain how educators can play a more productive role in ensuring that policy goals are achieved. Educators provide their views on their role as condom promotion agents, their perception of demand and utilisation among learners, as well as their insights on suitable distribution mechanisms in the school setting. Trepidation exists among educators about their roles in the promotion and education of condoms. Educator statements suggest that they see the value in their policy-ascribed role to deliver sexual health messages and are also open to performing a role in the distribution of condoms at schools. However, our findings reveal that their role as policy communicators or "street-level bureaucrats" is complicated by inadequate policy guidance. We therefore conclude that to achieve optimal outcomes in terms of safer sexual practices among learners, condom messaging and distribution mechanisms in school settings require evidence-informed implementation strategies.